Figur Ayah dalam Novel “Di Tanah Lada” Karya Ziggy Zezsyazeoviennazabrizkie melalui Pendekatan Semiotika Roland Barthes - Aina Siti Ghaisani (Gunung Djati Conference Series, 2023)
The focus and purpose of this research is to analyze the figure of a father in the novel Di Tanah Lada by Ziggy Z through Roland Barthes' semiotic approach. This study uses a qualitative descriptive method that applies a literature study. The objects in this study are several parts of the novel Di Tanah Lada 2nd printing. Based on the analysis that has been done, the research results show that this novel presents stories of domestic violence from the point of view of young children who are still innocent. The storyline presented focuses on the main character's journey with a family that is not harmonious due to violence perpetrated by a father figure. The myth that exists is that an unfavorable father figure can have a negative impact on the child's mindset and perception. In addition, the implications that arise make the family disharmonious and affect the well-being of children's lives. This study suggests readers to take the positive side of the novel Di Tanah Lada, namely a message to parents not to commit violence against children which can interfere with the development of their mindset and perceptions.